2019
DOI: 10.1002/app.47451
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ultrasonic extrusion of star styrene‐butadiene rubber on properties of carbon black‐ and silica‐filled compounds and vulcanizates

Abstract: Extrusion of star styrene‐butadiene rubber (SBR) without and with ultrasonic treatment at amplitudes 3.5, 5, 7.5, and 10 μm was carried out. The molecular structure of untreated and treated star SBR was determined. Significant reduction of die pressure was observed during ultrasonic treatment due to the thixotropic and degradation effects. Ultrasonic treatment of star SBR at 3.5 μm created molecules of higher molecular weight via long‐chain branching without gel formation. Ultrasonic treatment of star SBR at 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…It can be used to devulcanize rubbers, decrosslink crosslinked plastics, improve homogeneity of rubber and plastic blends, improve dispersion of fillers in polymer compounds, change crystallization of polymers, facilitate polymer functionalization and improve processability of polymers. Ultrasonic extrusion of rubbers such as NR, SBR, and BR have been studied extensively. These studies indicated that ultrasonic extrusion of these rubbers causes chain scission and degradation.…”
Section: Introductionmentioning
confidence: 99%
“…It can be used to devulcanize rubbers, decrosslink crosslinked plastics, improve homogeneity of rubber and plastic blends, improve dispersion of fillers in polymer compounds, change crystallization of polymers, facilitate polymer functionalization and improve processability of polymers. Ultrasonic extrusion of rubbers such as NR, SBR, and BR have been studied extensively. These studies indicated that ultrasonic extrusion of these rubbers causes chain scission and degradation.…”
Section: Introductionmentioning
confidence: 99%
“…The devulcanazation of SBR contained carbon black (CB) was also investigated. [30][31][32] It was performed by an extruder equipped to an ultrasonic die. It was claimed that the revulcanized samples prepared from devulcanized SBRs had close properties to the virgin rubber.…”
Section: Introductionmentioning
confidence: 99%
“…The results show that the ionic liquid can effectively improve the dispersion of silica in SBR, and can also improve the mechanical properties, wear resistance of the composites, the rolling resistance, and wet skid resistance of SBR. Liang and Isayev 10 performed ultrasonic treatment on the star-shaped SBR. The treated SBR has long chain branches and gel, which enhances the interaction between SBR and filler and the mechanical properties of the composite material.…”
Section: Introductionmentioning
confidence: 99%